2009
DOI: 10.1364/oe.17.012960
|View full text |Cite
|
Sign up to set email alerts
|

Creating negative refractive identity via single-dielectric resonators

Abstract: From a periodic array of commercially available zirconia cubes, we demonstrate artificial magnetic and electric dipoles due to the combination of displacement currents and Mie resonance. By scaling the size and periodicity of these dielectric resonators, the corresponding magnetic and electric responses are shifted to the desired frequencies. To further overlap the magnetic and electric resonances in the same frequency, we create a negative refractive index medium (NRIM) from single-dielectric resonators. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…However, it is inconvenient to fabricate NRIM for practical devices with either of these approaches owing to the multiple-step fabrication process. Therefore, Vendik and Gashinova have theoretically investigated the possibility that the effective isotropic negative refractive index medium is realizable through the use of two different dielectric sphere lattices embedded in a dielectric matrix [80], and in this regard, experimental verification has been completed recently [21,81]. The underlying physics is explicit since the magnetic fundamental resonance mode and electrical resonance mode can be overlapped by scaling the size and the lattice of the dielectric inclusions.…”
Section: High-permittivity Dielectric Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is inconvenient to fabricate NRIM for practical devices with either of these approaches owing to the multiple-step fabrication process. Therefore, Vendik and Gashinova have theoretically investigated the possibility that the effective isotropic negative refractive index medium is realizable through the use of two different dielectric sphere lattices embedded in a dielectric matrix [80], and in this regard, experimental verification has been completed recently [21,81]. The underlying physics is explicit since the magnetic fundamental resonance mode and electrical resonance mode can be overlapped by scaling the size and the lattice of the dielectric inclusions.…”
Section: High-permittivity Dielectric Compositesmentioning
confidence: 99%
“…It has been shown that negative permeability can be accomplished through a variety of approaches: for instance, inductive patterns such as split-ring resonators as first proposed by Pendry [16], circuit loops connected to microelectronics [17], Swiss rolls [18], pairs of conducting elements called sandwich structures [19,20], high permittivity-based dielectric composites [21], and many others [22,23]. In these fields, researchers should craft intuitive representations identifying the factors that make possess negative permeability in a given frequency range, and also, researchers should compute the value of permeability according to so-called retrieval procedures within these artificial magnetic structures [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is very meaningful to carry out in-depth investigations on all-dielectric metamaterial absorbers. In recent years, the research of dielectric metamaterials has witnessed remarkable progresses in theory, [16][17][18][19][20] experiment, [21][22][23] and applications. [24][25][26][27][28] These provide a good foundation for the study of dielectric metamaterial absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, artificial magnetism can be also produced via Mie resonance of dielectric particles with relative high permittivity [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. From Mie theory [24][25][26], it can be analytically demonstrated that the electromagnetic wave interaction of dielectric particles may exhibit a strong magnetic or electric resonances.…”
Section: Introductionmentioning
confidence: 99%
“…From the oscillation of resulting magnetic/electric dipole, negative permeability/permittivity may be produced. Compared to conventional planar SRR and related structures, Mie resonance metamaterial does not suffer from conductive currents and capacitance gap, so that it can be expected to generate low loss isotropic metamaterial structure [35][36][37][38][39][40][41]. This advantage is more remarkable at THz and optical regime owing to the limitation of high inductive loss and kinetic inductance of electrons [38][39][40].…”
Section: Introductionmentioning
confidence: 99%